Endosonography can detect residual tumour infiltration after medical treatment of oesophageal cancer in the absence of endoscopic lesions. Issue 11 (November 1992) - Nousbaum, J B; Robaszkiewicz, M; Cauvin, J M; Calament, G; Gouerou, H
Abstract : Endoscopic ultrasound (endosonography) is useful in the preoperative staging of oesophageal tumours. It may also have a role in evaluation and surveillance of patients with inoperable carcinomas. Thirty four patients with inoperable oesophageal cancer were investigated by endosonography and computed tomography before medical treatment. In 10 patients receiving combined chemotherapy and radiotherapy, the endoscopic lesions resolved and biopsy specimens were negative. When endosonography suggested the persistence of tumour infiltration in these patients, a local recurrence or distant metastases appeared within a few months. In contrast, when no infiltration was detected, no tumoral recurrence or progression was observed within eight months. These results suggest that endosonography is better than endoscopic biopsy specimens and computed tomography in assessing the response of oesophageal carcinoma to non-surgical treatment.